PARTICIPATORY PARADIGM OF WATERSHED DEVELOPMENT PROJECTS IN SEMI-ARID TROPICS OF ANDHRA PRADESH: AN ASSESSMENT - S. L. PATIL; MONDAL, BISWAJIT; G. L. BAGDI; BASAPPA , K. CHANNA; REDDY, K. K. (The Bioscan, 2018)
Watershed is a geohydrological unit for land and water resources development in rural areas which mainly emphasized on technology aspects rather than management of processes or its’ stakeholders. This paper presents the relative performance among the watersheds implemented by government organizations and non-government organizations (NGOs) through emphasizing people’s involvement in different phases of implementation. The results indicated that the watershed development team which is responsible for technical precisions of structures are better organized in government organization, but stakeholder institutions were weak in contrast to the watershed project developed and managed by NGOs. Overall, the government organization and NGO managed watersheds were able to fulfill about 55% and 67% of the possible components of participatory paradigm that indicated the need of further refinement and inclusion of participatory aspects while implementing the watershed programmes for better acceptability and sustainability of the programmes.